2017
DOI: 10.1111/imr.12510
|View full text |Cite
|
Sign up to set email alerts
|

Survivors Remorse: antibody‐mediated protection against HIV‐1

Abstract: Summary It is clear that antibodies can play a pivotal role in preventing the transmission of HIV-1 and large efforts to identify an effective antibody-based vaccine to quell the epidemic. Shortly after HIV-1 was discovered as the cause of AIDS, the search for epitopes recognized by neutralizing antibodies became the driving strategy for an antibody-based vaccine. Neutralization escape variants were discovered shortly thereafter, and, after almost three decades of investigation, it is now known that autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 201 publications
(406 reference statements)
1
37
0
Order By: Relevance
“…[264] Moreover, long-term treatment can also develop a variety of side effects, including lipodystrophy, hyperlipidemia, and damage to the liver and immune system. [266] In this case, nanomaterials can enhance the therapeutic effect of HIV vaccine as adjuvants or carriers. Scientists have suggested that HIV vaccine might be a new hope to eliminate virus by boosting immune response.…”
Section: Nanoparticle Vaccine For Hivmentioning
confidence: 99%
“…[264] Moreover, long-term treatment can also develop a variety of side effects, including lipodystrophy, hyperlipidemia, and damage to the liver and immune system. [266] In this case, nanomaterials can enhance the therapeutic effect of HIV vaccine as adjuvants or carriers. Scientists have suggested that HIV vaccine might be a new hope to eliminate virus by boosting immune response.…”
Section: Nanoparticle Vaccine For Hivmentioning
confidence: 99%
“…However, there is little direct evidence that nnAbs exert selective pressure on HIV-1 during infection in vivo (Burton et al, 2011; Chung et al, 2011; Santra et al, 2015). Vaccination studies in non-human primates (NHP) have suggested a role for non-neutralizing immune responses in protection against SIV or SHIV infection, but a causal link has not been proven experimentally (reviewed in (Lewis et al, 2017)). In these NHP studies, different vaccination strategies induced nnAb responses that correlated with protection from infection (Barouch et al, 2015; Barouch et al, 2013; Demberg et al, 2007; DeVico et al, 2007; Florese et al, 2009; Fouts et al, 2015; Hidajat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we defined Epitope Cluster A as a potent ADCC target recognized by CD4i mAbs (Guan et al, 2013). Epitope Cluster A maps to the inner domain and the extended N-, C-termini of gp120 ((Acharya et al, 2014; Gohain et al, 2015) and reviewed in (Lewis et al, 2014; Lewis et al, 2017a; Veillette et al, 2016)). Antibodies specific for Cluster A epitopes were shown to mediate the majority of the ADCC activity detected in chronically-infected individuals (Ferrari et al, 2011; Guan et al, 2013; Veillette et al, 2014) as well as being implicated in protection for the clinical RV144 vaccine trial (Bonsignori et al, 2012; Haynes et al, 2012; Tomaras et al, 2013) and our SHIV challenge studies in rhesus macaques (DeVico et al, 2007; Fouts et al, 2015) immunized with a gp120 transition state vaccine (Fouts et al, 2000).…”
Section: Introductionmentioning
confidence: 99%